Photovoice: An Evaluation of the Students’ Participation in Stay at Home, Magtanom Outreach Program - Maria Aurora Caballero; Raul Burce (MASI Mandiri Edukasi, 2025)
Conducted in the Philippines during the COVID-19 pandemic, this study employed Photovoice as a participatory platform for Civic Welfare Training Service (CWTS) students to express their experiences and evaluate their SAHMOP training in Partido State University at the foot of Mount Isarog and near coastal areas. Photovoice was also employed to collect and document students’ reflections on their experiences with home gardening, family participation, and civic engagement under the NSTP framework. It looked at and interpreted images to understand positive volunteer work, civic awareness, discipline, and proactive efforts. Among the 900 CWTS students trained under SAHMOP, 596 completed ten vegetable gardening stages. During the photovoice exhibit, students from marginalized communities expressed that the training fostered a sense of belonging and civic responsibility. One student reflected,